Drosophila melanogaster: A Model Organism to Study Cancer - Mirzoyan, Zhasmine; Sollazzo, Manuela; Allocca, Mariateresa; Valenza, Alice Maria; Grifoni, Daniela; Bellosta, Paola (Frontiers in Genetics, 2019)
Cancer is a multistep disease driven by the activation of specific oncogenic pathways concomitantly with the suppression of tumor suppressor genes that act as sentinels to control physiological growth. The conservation of most of these signaling pathways in Drosophila, and the ability to easily manipulate them genetically, has made the fruit fly a useful model organism to study cancer biology. In this review we outlined the basic mechanisms and signaling pathways conserved between humans and flies responsible of inducing uncontrolled growth and cancer development. Second, we described classic and novel Drosophila models used to study different cancers, with the objective to discuss their strengths and limitations on their use to understand growth cell autonomously and within organs, and their use for drug screens aimed at the discover of therapeutic approaches.